1996
DOI: 10.1007/bf02815207
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic studies in autism and related disorders

Abstract: The major histocompatibility complex comprises a number of genes that control the function and regulation of the immune system. One of these genes, the C4B gene, encodes a product that is involved in eliminating pathogens such as viruses and bacteria from the body. We previously reported that a deficient form of the C4B gene, termed the C4B null allele (no C4B protein produced) had an increased frequently in autism. In this study we attempted to confirm the increased incidence of the C4B null allele in autism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 7 publications
2
48
0
3
Order By: Relevance
“…Autism and the immune system have been linked genetically and symptomatically (Warren et al, 1996;van Gent et al, 1997;Krause et al, 2002). Recent studies have shown that normal neurons in developing and adult brains express proteins of the major histocompatibility complex (MHC) class I, known for their role in the immune system (Corriveau et al, 1998;Huh et al, 2000).…”
Section: Linking Altered Structure and Function With Altered Neural Dmentioning
confidence: 99%
“…Autism and the immune system have been linked genetically and symptomatically (Warren et al, 1996;van Gent et al, 1997;Krause et al, 2002). Recent studies have shown that normal neurons in developing and adult brains express proteins of the major histocompatibility complex (MHC) class I, known for their role in the immune system (Corriveau et al, 1998;Huh et al, 2000).…”
Section: Linking Altered Structure and Function With Altered Neural Dmentioning
confidence: 99%
“…18,19 Among the genes implicated in autism, several relate to immune regulation and function, including HLA-antigen presentation molecules and components of the complement system. 14,[20][21][22][23][24][25][26][27] Although abnormalities of cytokines and chemokines have been reported in the blood of patients with autism including plasma levels of tumor necrosis factor-a (TNF)-a, TNF receptor II, Interferon-gamma (IFNg), Interleukin-12 (IL-12), and IL-10, no definitive profile has emerged. Indeed, the changes reported in cytokine levels may occur in separate subgroups of autism subjects that have different clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…No genetic studies have been reported for prominent metalsusceptibility enzymes delta-aminolevulinic acid dehydratase (ALAD), coproporphyrinogen oxidase (CPOX), and stannin (SNN). Bias in histocompatibility haplotypes [29][30][31][32][33] may be indicative of exogenous infectious or inflammatory agents as contributory factors in autism.…”
Section: Genetic and Biochemical Markers In Asdmentioning
confidence: 99%
“…Gastrointestinal anomalies are frequent: in one study, 91% of ASD subjects were affected [128] . Inflammatory processes taking place in gut, compounded by immune system deficiencies [30,[129][130][131][132] may contribute to brain inflammation in ASD.…”
Section: Internal Sensingmentioning
confidence: 99%